Analysis of Charismatic and Transformational Leadership in the Phase of Resource Constraints: An Analytical Study of SMPIT AL ITQON - Nur Atik Azkiyah; Bayan Rahman; Hasyim Asy’ari; Jejen Musfah (al-Afkar, Journal For Islamic Studies, 2026)
This article analyzes the application of charismatic and transformational leadership in managing limited resources at SMPIT AL ITQON. This research is focused on identifying how the two leadership styles affect organizational performance, educators' motivation, and adaptation strategies applied in the midst of limited resources.  A qualitative approach with data collection techniques through in-depth interviews, participatory observation, and document analysis was used in this study. The results showed that the combination of these two leadership styles was proven to increase the efficiency of resource management, create a supportive work environment, and strengthen commitment to organizational goals. This study has concluded that the integration of charismatic and transformational leadership is an effective strategy in overcoming resource limitations.